Effect of a high angle grain boundary on deformation behavior of Al nanopillars. (October 2015) - Kim, Youbin; Lee, Subin; Jeon, Jong Bae; Kim, Yong-Jae; Lee, Byeong-Joo; Oh, Sang Ho; Han, Seung Min
Graphical abstract: Abstract : The effect of inclusion of a grain boundary in nanopillar was studied using Al bicrystal with [3 4 3]/[ 13 17 ‾ 14 ] orientation. Ex situ compression results showed higher strengths in bicrystal pillars than in single crystal pillars, which is explained with respect to the reduced single-armed source length that was confirmed in the in situ TEM tests. Molecular dynamics simulations indicated that the grain boundary can assist in dislocation nucleations without resulting in dislocation pile-up at the boundary.